1999
DOI: 10.1002/(sici)1521-4141(199906)29:06<1955::aid-immu1955>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity relationships within the N-terminal short consensus repeats (SCR) of human CR1 (C3b / C4b receptor, CD35): SCR 3 plays a critical role in inhibition of the classical and alternative pathways of complement activation

Abstract: Genes coding for between one and four short consensus repeats (SCR) of the N‐terminal region of human complement receptor 1 (CR1) were synthesized from oligonucleotides and those encoding SCR(1 – 2), SCR(1 – 3), SCR(1 – 4), SCR3 and SCR(3 – 4) were expressed as inclusion bodies in Escherichia coli. Following solubilization in urea, the proteins were partially purified and refolded and the activity of each protein was assessed in both classical and alternative pathway complement assays. All fragments showed a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…The gene coding for the N-terminal SCR1-3 of LHR-A of CR1 with a codon for an additional C-terminal cysteine was constructed as described by Dodd and colleagues, 17 and a plasmid, pDB1081-1 constructed as described in Mossakowska and colleagues 11 for transformation into the expression host Escherichia coli BL21 (DE3). The protein product of the expression vector was purified and shown to inhibit antibody-sensitized red blood cell lysis by human serum, to inhibit C3a release, and to function as a co-factor for Factor I.…”
Section: Design Of a Recombinant Low-molecular Weight Complement Regumentioning
confidence: 99%
See 4 more Smart Citations
“…The gene coding for the N-terminal SCR1-3 of LHR-A of CR1 with a codon for an additional C-terminal cysteine was constructed as described by Dodd and colleagues, 17 and a plasmid, pDB1081-1 constructed as described in Mossakowska and colleagues 11 for transformation into the expression host Escherichia coli BL21 (DE3). The protein product of the expression vector was purified and shown to inhibit antibody-sensitized red blood cell lysis by human serum, to inhibit C3a release, and to function as a co-factor for Factor I.…”
Section: Design Of a Recombinant Low-molecular Weight Complement Regumentioning
confidence: 99%
“…17 The analysis of activity revealed that the 21-kd SCR1-3 fragment was active against both the classical and alternative pathways and appeared to be correctly folded. 11,13,17 …”
Section: Design Of a Recombinant Low-molecular Weight Complement Regumentioning
confidence: 99%
See 3 more Smart Citations